(3cTa GdZeI aj GdQO Ydi ef Mce HcaQ CWaGd Cgd GdPeIs ((3eMeO Hf GdYeGO GdMfai s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf (B,(3HYO ahGbYI UOQJ ef MGce TGaYi s
(3BNQgG (B:s
(3hHGbi GdeSCdI eYQha hGdMeO ddg hMOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdSGHY hGdYTQhfs
(3hgj CLhHI dLeGYI ef GdabgGA Ydi hGbYI UOQJ ef MGce TGaYi jbGd dg (B: (3MSf Hf GdSGFM ai SfI (B857 (3g`s
(3hgj Cfg Mce HHbGA CWaGd GdjghO hGdfUGQi Ydi Ojfge Edi Mjf HdhZges
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdCSJGP GdOcJhQ GSMGb ehSi GdMSjfi GdNGUI s
Keywords: (3Gdabg GdTGaYjs